Ocular side effects of levitra ® (vardenafil) - results of a double-blind crossover study in healthy male subjects - Roessler, Gernot; Vobig, Michael; Walter, Peter; Mazinani, Babac AE (Drug design, development and therapy, 2019)
To determine ocular side effects of vardenafil with special regard to color vision and retinal function. This was a single center, randomized, double-blind, placebo-controlled, twofold crossover study with an administration of a single oral dose of two 20 mg tablets of BAY 38-9456 (vardenafil hydrochloride) or corresponding placebo in 24 healthy male subjects. Ocular investigations included Farnsworth-Munsell D100 color vision test, electroretinogram, and basic ophthalmological examinations like visual acuity, visual field, and slit-lamp of anterior segment and fundus. Compared to placebo, administration of vardenafil hydrochloride lead to a temporary significant increase of Farnsworth-Munsell D100 total error score after 1 and 6 hours as well as in error lines 3 and 4 after 1 hour. Twenty-four hours after administration there was no significant alteration of total error score or of any error line. While latency of electroretinogram b-wave remained unaffected, amplitudes showed a significant decrease compared to placebo 1 hour following administration. While other ocular examinations did not reveal any differences in general some mild to moderate but no serious adverse events have been reported. Despite temporary changes in retinal function our study reports good tolerability of vardenafil in regard to ocular side effects.